A new species of Arthrographis (Eremomycetaceae, Dothideomycetes), from the soil in Guizhou, China - Li, Xin; Zhang, Zhi-Yuan; Chen, Wan-Hao; Liang, Jian-Dong; Huang, Jian-Zhong; Han, Yan-Feng; Liang, Zong-Qi (Phytotaxa, 2022)
During a survey of keratinolytic fungi in China, a new species, Arthrographis multiformispora was isolated from soil samples. Morphologically, A. multiformispora differs from other species in the genus by the presence of globose or subglobose chlamydospores and cylindrical arthroconidia. Phylogenetically, our four strains were clustered together with high support values and separated from other clades. We provided a description, illustrations, and phylogenetic tree for the new species.